Index of the satisfaction of public library services in the context of the quality of life: the Lithuanian counties’ public libraries case study - Pečeliūnaitė, Angelė (Information & Media, 2017)
The article deals with the problem related to the impact of public libraries’ services on the consumer. The paper presents the summarized results of the independent research (the quality of life interface between library activities and community members) – the index of the satisfaction of services (IS) of the Lithuania counties’ public libraries in the context of quality of life. The index was calculated with an evaluate of the weights of the services, coupled with the impact on quality of life. It was determined that the general index of satisfaction with information services is the largest, but it should be noted that active users are more satisfied with the training organized by the library. Currently, the impact of training on the quality of life is very significant, as it increases social inclusion, reduces information exclusion and strengthens self-confidence. The statistical analysis showed that the IS does not differ significantly between the different Lithuania counties’ public libraries, but statistically significantly depends on the demographic data of population. It is noticed that the competence and helpfulness of librarians was most strongly felt in direct contact, so it largely due to exposure to greater satisfaction with the services, and we believe that effective communication is an additional factor that increases IS. It is important to notice that the impact of the Lithuanian counties’ public libraries services on the consumer’s quality of life is significant. We can confirm the statement that public libraries are a good business for the society.
Keywords: ...